The serial mediating effects of moral resilience and moral courage on the relationship between moral injury and positive coping style in Chinese nursing interns - Zhang, Ruixin; Wang, Xue; Chen, Jie; Zhang, Shulin; Li, Ying (Frontiers in Psychology, 2025)
BackgroundClinical practice is a necessary experience for nursing students to become qualified nurses. The impact of moral injury on nursing interns’ coping styles remains unclear. This study aimed to explore the correlation between moral injury and positive coping style among nursing interns in clinical practice and to examine the mediating roles of moral resilience and moral courage on this correlation.MethodsA convenience sample of nursing interns (n = 1,122) from 6 nursing schools in the Southwest China were recruited using social media platforms. The Chinese version of Moral Injury Symptom Scale: Healthcare Professionals Version, Simplified Coping Style Questionnaire, Rushton Moral Resilience Scale and Nurses’ Moral Courage Scale were used to collect data from February 1 to April 15, 2024. Regression-based mediation analysis was used to distinguish the direct effect of moral injury on positive coping style, and the indirect effect mediated by moral resilience and moral courage.ResultsMoral injury was negatively associated with moral resilience (r = −0.463, P < 0.001), moral courage (r = −0.226, P < 0.001) and positive coping scores (r = −0.235, P < 0.001). Moral resilience was positively correlated to moral courage (r = 0.184, P < 0.001) and positive coping scores (r = 0.196, P < 0.001). Moral courage was positively associated with positive coping scores (r = 0.515, P < 0.001). The mediation effect test indicates that moral injury can directly influence positive coping (p < 0.01), with the direct effect accounting for 46.61% of the total effect. Additionally, moral injury can indirectly influence positive coping through the mediating effects of moral resilience and moral courage, as well as through the sequential mediation of both. The mediation effects account for 18.64%, 23.73% and 11.02% of the total effect, respectively.ConclusionMoral injury is negatively correlated with positive coping style of nursing interns in China, and moral resilience and moral courage may buffer the negative effects of moral injury and improve the coping strategies.